Extinction in a generalized Lotka-Volterra predator-prey model. (2000) - Ackleh, Azmy S.; Marshall, David F.; Heatherly, Henry E.
Abstract : In this paper we discuss the asymptotic behavior of a predator-prey model with distributed growth and mortality rates. We exhibit simple criteria on the parameters which guarantee that all subpopulations but one predator-prey pair are driven to extinction as t → ∞ . Finally, we present numerical simulations to illustrate the theoretical results.